Perbaikan Proses Penerimaan Spare Part dengan Menghilangkan Peran Gudang Main Store: A Case Study - Kristina Halim; Herry Christian Palit (Jurnal Titra, 2016)
PT.Y is a company that produce cigarette. Currently PT.Y wants to revise the spare part receiving system that was applied. Spare part receiving process first start at main store, then will be delivered to sub store. The improvement that wants to be applied is to eliminate the main store, so that spare part can be delivered directly to warehouse sub store. By portraying the current process using value stream mapping, two waste could be eliminated if warehouse main store role is erased. Unnecessary transportation and over processing is the occurring waste in these process. The proposed counter measure is to change all store location for all material in the data base so that when PR was created the store location will automatically determine the real receiving warehouse. The proposed counter measure can shorten the processing time by 16.918,91 second per day. Counter measure can also decrease transportation fees by Rp.6.140,00 per day.